2020
DOI: 10.1097/pai.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a Dual (Immunohistochemistry and Fluorescence In Situ Hybridization) HER2/neu Testing Strategy on Invasive Breast Cancers

Abstract: The American Society of Clinical Oncology and the College of American Pathologists recommend that human epidermal growth factor receptor 2 (HER2)/neu status be determined for all invasive breast cancers. Although the most commonly used modalities to determine HER2/neu status, immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), generally give concordant results, a small but consistent discordance rate between them has been demonstrated in prior studies. Most institutions in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Although further studies are required to identify the prognostic impact of this group, performing both HER2 IHC and ISH simultaneously would be necessary to ensure that the patients do not miss the chance to receive adequate therapy. Our study showed a similar proportion of HER2 IHC/SISH discordance seen in previous studies [ 29 ] and suggested that dual testing was more cost-effective than the current IHC-first strategy.…”
Section: Discussionsupporting
confidence: 87%
“…Although further studies are required to identify the prognostic impact of this group, performing both HER2 IHC and ISH simultaneously would be necessary to ensure that the patients do not miss the chance to receive adequate therapy. Our study showed a similar proportion of HER2 IHC/SISH discordance seen in previous studies [ 29 ] and suggested that dual testing was more cost-effective than the current IHC-first strategy.…”
Section: Discussionsupporting
confidence: 87%
“…22,28,29 Some laboratories practice reflex testing, that is, referral for HER2 FISH only on HER2 IHC score = 2+ cases, whereas others adopt a dual testing approach, that is, HER2 IHC and FISH are performed on all invasive breast carcinomas. Hariri et al 30 suggested that although reflex testing costs less, it may be less effective than a dual testing strategy. They showed that some (n = 6) breast tumors that were HER2 IHC-positive tested HER2 FISHnegative, and others (n = 16) that were HER2 IHCnegative were actually amplified on HER2 FISH testing.…”
Section: Discussionmentioning
confidence: 99%
“…Hariri et al 30 suggested that although reflex testing costs less, it may be less effective than a dual testing strategy. They showed that some (n = 6) breast tumors that were HER2 IHC-positive tested HER2 FISH-negative, and others (n = 16) that were HER2 IHC-negative were actually amplified on HER2 FISH testing 30 . However, in a resource-constrained setting, reflex testing remains the favored approach.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that FISH analysis should be performed when inconclusive IHC/IF results are observed. However, a dual testing strategy could also be employed whereby both IHC and FISH are implemented simultaneously, similarly to a new cost-effective HER2 screening strategy developed for invasive breast cancer [ 2 , 64 ]. Interestingly, new artificial intelligence-based algorithms are now being developed for automated detection and localization of PTEN loss, which have shown high accuracy in prostate cancer IHC stained sections and could further streamline PTEN screening [ 65 ].…”
Section: Pten Status As a Predictive Biomarker For Prostate Cancermentioning
confidence: 99%